“Evaluación de complejos micorrízicos asociados al cultivo de plántulas de café (Coffea canephora)”. - Gavilanes Velasco, Adrián Steffano (2019)
SUMMARY The objective of this investigation was to evaluate the mycorrhizal complexes associated with the cultivation of coffee seedlings (Coffea canephora). The work was carried out in the lands of mr. Second Velasco Velóz, located at Kilometer 5 ½ of Vía Montalvo - Carmen Rosa. Robusta coffee variety was used with an experimental design of randomized complete blocks, with 6 treatments and 3 repetitions, for the evaluation and comparison of measures of treatments was performed with the Tukey test at 95% probability. These treatments consisted of Bioremec 3 g / plant, Micobacter 3 g / plant, Micor 3 g / plant, Micopalm 3 g / plant, Faciag 3 g / plant, Testigo 5 g / plant, A microbiological analysis was carried out prior to the establishment of the trial, the necessary tasks for the development of the nursery were: sowing, transplanting, application of mycorrhizae (at the time of the transplant in doses of 3g / plant), weed control, phytosanitary control, irrigation, fertilization, pruning and defoliation. To estimate the effects of the treatments, the following variables were taken: plant height, leaf emission, stem diameter, leaf length, foliar area at 60 and 90 days after transplant, root length, root biomass, percentage of colonization of mycorrhizae, count of mycorrhizal spores, analysis of mycorrhizal population and economic analysis at 120 days after transplantation. The results determined that the applications of the different types of mycorrhizae affected the growth and development of the seedlings in the nursery, stimulating the increase of biomass and root length. The best treatment was Micor at a dose of 3 g / plant compared to the control treatment. Regarding the economic analysis, it was observed that the highest utility was obtained with the Micobacter treatment in doses 3 gr / plant with $ 1345.5. Keywords: Robust coffee, Mycorrhiza, Glomus, Inoculation, Mycorrhizal colonization.